THE INTERCONNECTION OF ARCHITECTURE AND MUSIC: HARMONY OF SPACE - Пісьо, Степан; Марусяк, Вікторія (SWorldJournal, 2025)
The article examines the fascinating transformation of two artistic worlds – architecture and music – into one harmonious ensemble. The authors explore how architectural forms and musical compositions can interact, creating new sensory impressions and dee